Comparative Proteomics of Meat Spoilage Bacteria Predicts Drivers for Their Coexistence on Modified Atmosphere Packaged Meat - Kolbeck, Sandra; Ludwig, Christina; Meng, Chen; Hilgarth, Maik; Vogel, Rudi F. (Frontiers in Microbiology, 2020)
Besides intrinsic and extrinsic factors such as antagonism for organic substrates or temperature, the storage atmosphere of meat has a high influence on the development of its initial microbiota. Specific modified atmospheres (MA) selectively supress growth of aerobic and anaerobic bacteria, thus reshaping the initial microbiota. As some microorganisms are more tolerant to MA, they overgrow competitors and produce metabolites that cause rejection of the product. Those organisms are called ephemeral spoilage organisms (ESO). In order to elucidate responses to different MA by means of metabolic adaptation and competition for organic substrates on meat, the typical representative meat spoilage bacteria Brochothrix (B.) thermosphacta TMW2.2101 and four lactic acid bacteria (LAB) Carnobacterium (C.) divergens TMW2.1577, C. maltaromaticum TMW2.1581, Leuconostoc (L.) gelidum subsp. gelidum TMW2.1618 and L. gelidum subsp. gasicomitatum TMW2.1619 were chosen. Bacteria were grown in sterile glass bottles filled with a meat simulation medium, which was aerated constantly with either air, 100%_N2, 30%_CO2/70%_O2 or 30%_CO2/70%_N2. Growth of bacteria during incubation at 25°C and stirring at 120 rpm was monitored over 48 hours and a label-free quantitative mass spectrometric approach was employed to determine changes within the bacterial proteomes in response to oxygen and carbon dioxide. Both Leuconostoc subsp. were intrinsically tolerant to MA, exhibiting no proteomic regulation of enzymes, whereas the other species provide a set of metabolic adaptation mechanism, enabling higher resistance to the detrimental effects of MA. Those mechanisms comprise: Enhanced oxidative stress reduction, adjustment of the pyruvate metabolism and catabolic oxygen consumption in response to oxygen and intracellular pH homeostasis, maintenance of osmotic balance and alteration of the fatty acid composition in response to carbon dioxide. We further evaluated the potential of industrial used MA to inhibit specific bacterial spoilage. No bacterial inhibition is predicted for 30%_CO2/70%_O2 for the analyzed species, whereas 30%_CO2/70%_N2 predictively inhibits C. divergens TMW21577 and B. thermosphacta TMW2.2101. Furthermore, species-specific metabolic pathways enabling different and preferential carbon source utilization were identified, which enable non-competitive coexistence of respective bacteria on meat, resulting in synergistic spoilage. In conclusion, this study gives mechanistically explanations of their acknowledged status as typical spoilage organisms on MAP meats.